Leadership styles and employee performance: innovativeness of organizational citizenship behavior for organizational effectiveness - Soo, Hooi Sin; Ali, Hassan (2016)
Leadership is a critical resource that helps organization to sustain organizational effectiveness either in public sector or in private sector.Leadership plays a strong influence on employee’s motivation, emotion, attitudes and performance as leaders have ability to transmit meaning to employees.However, different leadership styles have different impacts on employee performance.Although it is demonstrated that leader is capable to produce positive outcomes for employee performance, but it is interesting to know how leadership can influence voluntary behaviors such as organizational citizenship behavior and thus further enhance organizational effectiveness. This paper seeks to provide a review in the literature for the effects of leadership on employee performance and the innovativeness of organizational citizenship behavior in order to inform the public sector to focus on emphasizing the development of leadership capacity among civil servants to improve public sector employee performance.